Normal mode sensitivity to Earth's D″ layer and topography on the core-mantle boundary: What we can and cannot see - Koelemeijer, P; Deuss, A; Trampert, J (Oxford University Press, 2012)
The core-mantle boundary (CMB) is Earth's most profound internal boundary separating the liquid iron outer core and the solid silicate mantle. The detailed structure near the CMB has a major influence on mantle convection and the evolution of the core. Seismic observations, such as topography on the CMB, thin ultra-low velocity zones (ULVZs), seismic anisotropy and the anticorrelation between shear wave and bulk sound velocity heterogeneities have mainly been made using body waves and are still poorly constrained. We investigate the sensitivity of Earth's free oscillations to these features and specifically show how large individual anomalies must be for them to be observable. In addition, we discuss the possible trade-offs between these different lowermost mantle structures. Although modes have strong sensitivity to all the structures inserted, the results illustrate the limits of what normal modes can resolve. Our tests show that: (i) Even small scale features, such as ULVZs, with a thickness larger than 19km can be observed as long as their distribution contains a long wavelength component. (ii) The peak-to-peak amplitude of CMB topography has a larger influence than its pattern and has to be smaller than 5km to fit the data. (iii) The effect of scaling between shear wave velocity and density anomalies is less constrained, but a laterally varying pattern is implied by a simple test, suggesting the presence of chemical variations. (iv) A strong trade-off exists between anisotropy in compressional wave velocity and incidence angle whereas shear wave anisotropy is less observable. These findings provide valuable information for future normal mode studies on structures in Earth's lowermost mantle and their trade-offs.